Peronema canescens as a Source of Immunomodulatory Agents: A New Opportunity and Perspective - Ahmad Hafidul Ahkam; Yasmiwar Susilawati; Sri Adi Sumiwi (Biology)
Immunomodulators are pivotal in managing various health conditions by regulating the immune response by either enhancing or suppressing it to maintain homeostasis. The growing interest in natural sources of immunomodulatory agents has spurred the investigation of numerous medicinal plants, including Peronema canescens, commonly known in Asia as sungkai. Traditionally used for its medicinal properties in Southeast Asia, Peronema canescens belongs to the Verbenaceae family and has garnered significant attention. This review discusses the immunomodulatory activity of the active compounds in Peronema canescens and explores the potential directions for future research.